2015
DOI: 10.15414/jmbfs.2015.5.1.68-72
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnesium D - Gluconate Fortification on Heat Stability of Goat’s Milk and Physicochemical Properties, Sensory Characteristic and Texture Profile of Yoghurts During Cold Storage

Abstract: Average consumption of magnesium in Poland does not satisfy people’s daily demand for this element; therefore it is necessary to supplement it. In the conducted experiment there was established the possibility of using magnesium D-gluconate for enriching yoghurts and goat’s milk. The highest dose of magnesium, which did not cause protein precipitation during pasteurization, was the addition of 20 mg of magnesium for 100 g of goat’s milk. Fortification with magnesium decreases pH and increases the hardness of y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Earlier studies showed that the addition of calcium chloride to goat's milk also increased the hardness of yoghurts. [43] Moatsou and Park [44] showed that the abundance of goat β-casein and α S1 -casein polymorphisms is the main feature of casein from goat's milk. Low casein content in goat's milk, low proportion of α S1 -casein, the lower sedimentation rate of casein micelles, higher β-casein solubility, higher content of calcium and phosphorus and lower thermal stability as compared with cow's milk causes poor texture of yoghurt.…”
Section: Parameters Of Texturementioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies showed that the addition of calcium chloride to goat's milk also increased the hardness of yoghurts. [43] Moatsou and Park [44] showed that the abundance of goat β-casein and α S1 -casein polymorphisms is the main feature of casein from goat's milk. Low casein content in goat's milk, low proportion of α S1 -casein, the lower sedimentation rate of casein micelles, higher β-casein solubility, higher content of calcium and phosphorus and lower thermal stability as compared with cow's milk causes poor texture of yoghurt.…”
Section: Parameters Of Texturementioning
confidence: 99%
“…In previous studies, it was shown that the addition of magnesium chloride also reduces the intensity of goaty taste and odor. [43] Park et al [30] stated that the two biggest barriers in marketing of goat milk products are negative public perception of goaty flavor and odor and seasonal milk production. The conducted studies showed that some magnesium salts, such as citrate, by reducing the intensity of goat's flavor and odor may increase the acceptability of fermented goat's milk.…”
Section: Organoleptic Parametersmentioning
confidence: 99%
“…In cheeses made from the milk enriched with calcium amino acid chelate no goaty taste were observed, which was the case in the control cheeses. Znamirowska et al [67] study showed that the addition of mineral compounds reduced the intensity of goat and sour taste in goat milk yoghurts during 21 days of cold storage. Cheeses with calcium amino acid chelate had a softer and more smeary texture than the control cheese.…”
Section: Organoleptic Evaluation Of Acid-curd Cheesementioning
confidence: 99%
“…Previous studies comparing different calcium salts, i.e., calcium chloride, calcium lactate, and calcium gluconate, found that the effect on pH, heat coagulation time, and ethanol stability varied depending on the type of salt used. [31][32][33] Milk acidity during fermentation (pH, OD 640 )…”
Section: Physicochemical Propertiesmentioning
confidence: 99%